Screening and expression of a silicon transporter gene (Lsi1) in wild-type indica rice cultivars - Sahebi, Mahbod; Musa, Mohamed Hanafi; Yusop, Mohd Rafii; Azizi, Parisa; Abiri, Rambod; Kalhori, Nahid; Atabaki, Narges (Hindawi Publishing Corporation, 2017)
Silicon (Si) is one of the most prevalent elements in the soil. It is beneficial for plant growth and development, and it contributes to plant defense against different stresses. The Lsi1 gene encodes a Si transporter that was identified in a mutant Japonica rice variety. This gene was not identified in fourteen Malaysian rice varieties during screening. Then, a mutant version of Lsi1 was substituted for the native version in the three most common Malaysian rice varieties, MR219, MR220, and MR276, to evaluate the function of the transgene. Real-time PCR was used to explore the differential expression of Lsi1 in the three transgenic rice varieties. Silicon concentrations in the roots and leaves of transgenic plants were significantly higher than in wild-type plants. Transgenic varieties showed significant increases in the activities of the enzymes SOD, POD, APX, and CAT; photosynthesis; and chlorophyll content; however, the highest chlorophyll A and B levels were observed in transgenic MR276. Transgenic varieties have shown a stronger root and leaf structure, as well as hairier roots, compared to the wild-type plants. This suggests that Lsi1 plays a key role in rice, increasing the absorption and accumulation of Si, then alters antioxidant activities, and improves morphological properties.